The Jews in Poland after the Second World War. Most Recent Contributions of Polish Historiography - Carla Tonini (Quest. Issues in Contemporary Jewish History, 2010)
In recent years Polish historians have shown a growing interest in the history of the Jews in Poland after 1945. Studies on this topic had started – although in a sporadic way - in the 1960s, intensified in the 1980s and at the turn of the twenty first Century they have focused on three main issues: post-war anti-Semitism; emigration and the creation of the State of Israel, and the restitution of property. The aim of this article is to set these studies in the Polish political and cultural context in which they were written in order to highlight elements of change and continuity within the historical debate.